SVPWM for 3-phase 3-level Neutral Point Clamped Inverter Fed Induction Motor Control - Palanisamy R; K. Vijayakumar (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
This paper gives Space Vector Pulse Width Modulation (SVPWM) for 3-phase 3-level Neutral Point Clamped (NPC) inverter fed induction motor control. A conventional two level inverter with 3-phase system has been developed for induction motor control. When it is applied for high voltage and power applications, which increases the voltage stress across the switch and harmonic content in the output. So multilevel inverter is much suitable for induction motor control, which provides nearly sinusoidal output voltage and diminished harmonic content in the output. Also the stator current of induction motor is minimsed, speed and torque of induction motor controlled with appropriate switching NPC inverter using SVPWM method. The proposed system simulation are verified using matlab simulink.